Reconsidering the goals of evolution education: defining evolution and evolutionary literacy - Kostas Kampourakis (Evolution: Education and Outreach, 2022)
Abstract In this paper, I argue that for both theoretical and practical purposes, it is useful for science education to clearly distinguish between science content knowledge and skills on the one hand, and the competencies related to their application in everyday life. This can be based on a distinction made by Douglas Roberts between two visions of literacy, and it can be effectively reconceptualized as the distinction between two types of literacy relevant to science: Science literacy, which is literacy relevant to the processes and products of science, related to the content of science taught in classrooms (literacy about issues within science); and Scientific literacy, which is literacy relevant to questions that students may encounter as citizens and to the socio-ethical implications of scientific knowledge (literacy about the implications of science for society). Based on this, we can in turn distinguish between two types of literacy related to evolution: Evolution literacy, which is literacy relevant to the evolution content taught in classrooms; and Evolutionary literacy, which is literacy relevant to questions that students may encounter as citizens and to the socio-ethical implications of scientific knowledge. In this article I argue that whereas a lot of attention has been given to evolution literacy as a learning goal, there has been less reflection and discussion about evolutionary literacy—and it is exactly the distinction between these two types of literacy that helps one realize this. Teaching for evolutionary literacy requires specific skills from teachers, which go beyond their ability to teach concepts and explanations. My aim is to initiate a discussion about how to set evolutionary literacy as a learning objective at schools along evolution literacy. A key issue in such a case is how we could prepare teachers who would be capable, and confident, to address issues going beyond the typical science content, and which are often related to worldviews, in the classroom.